Implementasi Produk Kebijakan Pendaftaran Tanah Aset Pemerintah Daerah Kabupaten Pasaman - Farda, Nessa Fajriyana; Syuryani, Syuryani; Amirullah, Imron; Sari, Ice Wahyuni Permata (eScience Humanity Journal, 2024)
The government/regional government land asset registration policy is the mandate of Article 43 of Government Regulation Number 27 of 2014 concerning Management of State/Regional Property which states that "State/regional property in the form of land must be certified in the name of the government of the Republic of Indonesia/regional government concerned". However, not all local governments have implemented it optimally. One of them is Pasaman district. This research aims to find out how the Pasaman district government's land asset registration policy is implemented and the obstacles it faces. This research is descriptive in nature and uses an empirical juridical approach. The research results show that the land that has not been certified in Pasaman district is mostly road land assets. Therefore, local governments cannot be separated from problems both internally and externally.